Application of Legal Sanctions Against Violations Carried out by fair in-vestors in the Indonesian capital market - Lucky Ferdilese; Ahmad Husaini; Mutiah Arfah Amaliah; Sri Untari Puji Astuti; Raja Rajuandar (LEGAL BRIEF, 2025)
Implementation of legal sanctions against violations committed by investors in the Indonesian capital market. The purpose of this study is to impose sanctions on legal violations committed by investors in the capital market, with the following problems: 1) How is the construction of the application of legal sanctions against violations committed by investors in the capital market?; 2) How are efforts to increase the effectiveness of imposing sanctions against Capital Market Crimes in Indonesia when linked through Law Number 21 of 2011 concerning the Financial Services Authority? The research method used is Normative with a Legislative approach and a Conceptual Approach that utilizes Primary Legal Materials and secondary legal materials. The results of the discussion of the reconstruction of legal sanctions, in the form of additional prison terms and an increase in the amount of fines for violations committed by investors, are very necessary to strengthen its existence, so that it can create a healthy and attractive economic climate for other investors to invest in Indonesia. The sanctions are regulated normatively in Article 101 of Law Number 8 of 1995 concerning the Capital Market. The conclusion is that the application of these sanctions is carried out to create substantive justice so that it can create a healthy economic climate and attract investor interest